O dialogismo na construção do discurso radiofônico: análise das tendências de massificação e diversificação da informação produzida na rádio CBN de Belo Horizonte - Rodrigo Marcio Cardoso Borges (2008)
The aim was to identify, understand and analyze the processes of selection of information and news production of the CBN radio station in Belo Horizonte, which is the object of research. It has intended to verify if these processes could incite a relative homogenization of the broadcast information. The research discusses if the virtual environments of big agencies of journalistic information have primacy compared with formal sources such as public organs, personal sources used by reporters and participation from listeners. This main line of research was complemented by the analysis of the use of information sources available on the Internet, with the purpose of verifying if the sources accessed by journalists are mostly the same. The following methodological tools were used in qualitative approach: case study, participant observation, semi-structured interview with the journalism manager of the radio station and discourse analysis. The research hasdemonstrated that the great amount of information provided by the public relations departments of public organs contribute to the homogenization of information. The participant observation has also revealed that the journalist tends to search for familiar sources, provided with credibility.